2022
DOI: 10.1111/jce.15622
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in patients with atrial fibrillation and heart failure undergoing catheter ablation compared to medical treatment: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Introduction Increasing evidence has suggested improved outcomes in atrial fibrillation (AF) patients with heart failure (HF) undergoing catheter ablation (CA) as compared to medical therapy. We sought to investigate the benefit of CA on outcomes of patients with AF and HF as compared to medical therapy. Methods and Results A systematic review of PubMed, Embase, and Cochrane Central Register of Clinical Trials was performed for clinical studies evaluating the benefit of CA for patients with AF and HF. Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…The indispensability of AF ablation in the management of patients with concomitant heart failure has been both shown in landmark trials and confirmed in meta-analyses. Indeed, a recent review [ 40 ] reported that, in the population of heart failure patients at functional stages I–III, catheter ablation decreases all-cause mortality and improves all-atrial arrhythmia recurrence rate as well as cardiac function when compared to medical management—findings are still inconclusive regarding the sickest heart failure patients, at functional stage IV. Focusing on CB ablation, long-term outcomes on functional stage and ejection fraction appear favorable and equivalent to those achieved with the RF-based approach [ 41 , 42 ].…”
Section: Patient Selection For Af Ablation Through Cryoablationmentioning
confidence: 99%
“…The indispensability of AF ablation in the management of patients with concomitant heart failure has been both shown in landmark trials and confirmed in meta-analyses. Indeed, a recent review [ 40 ] reported that, in the population of heart failure patients at functional stages I–III, catheter ablation decreases all-cause mortality and improves all-atrial arrhythmia recurrence rate as well as cardiac function when compared to medical management—findings are still inconclusive regarding the sickest heart failure patients, at functional stage IV. Focusing on CB ablation, long-term outcomes on functional stage and ejection fraction appear favorable and equivalent to those achieved with the RF-based approach [ 41 , 42 ].…”
Section: Patient Selection For Af Ablation Through Cryoablationmentioning
confidence: 99%
“…This confusion is reflected in the widespread variation in the use of AF ablation across and within given geographies. 36,37 Fortunately, several prospective, randomized studies comparing AF ablation to usual care approaches (AATAC, AMICA, ARC-HF, CABANA, CAMERA-MRI, CAMTAF, CASTLE-AF, RAFT-AF, PABA, CAS-TLE HTx) 26,31,[38][39][40][41][42][43][44][45][46] and meta-analyses [47][48][49][50][51][52][53][54] have been performed to provide clinicians with information and minimize uncertainty.…”
Section: Esc and Hrs Guidelines Classify Af Ablation In Hf Patients A...mentioning
confidence: 99%
“…Fortunately, several prospective, randomized studies comparing AF ablation to usual care approaches (AATAC, AMICA, ARC‐HF, CABANA, CAMERA‐MRI, CAMTAF, CASTLE‐AF, RAFT‐AF, PABA, CASTLE HTx) 26,31,38–46 and meta‐analyses 47–54 have been performed to provide clinicians with information and minimize uncertainty.…”
Section: Literature Review Of Prospective Randomized Trials Comparing...mentioning
confidence: 99%
“…The study did not include non-HF patients undergoing cryoballoon ablation or a comparable group of those HF patients undergoing radiofrequency ablation for AF or a medication-only group. 23,24 The study did not assess symptom recovery, NYHA class, or quality of life after the follow-up period. 11 The LVEF groups of HF patients were stratified based on the LVEF determined on echocardiography before the procedure time, and the value of LVEF might have changed according to recent HF onset and management thereafter.…”
Section: Study Limitationsmentioning
confidence: 99%